The Effect of Husbands’ Support on Mothers’ Family Planning in Dayak Tribe - Evy Nurachma; Nina Mardiana (Indonesian Journal of Multidisciplinary Science, 2022)
The Dayak tribe has a fairly strong magical heritage. The spiritual sciences became a typical symbol of the tribal customs that inhabited the interior of the land of Borneo. F the factors that hinder the development of birth control are the Supernatural World for Dayak Tribe The leaves of dong quai can be material to prevent pregnancy in a very natural way. but the factor of lack of support from the husband greatly affects the attitude of the mother in the  Dayak tribe environment in using contraceptives, Purpose, knowing the influence of husband support on the attitude of mothers in birth control in Pampang Village. The design of this study is cross sectional. The sample used was 47 respondents. The sampling technique uses purposive sampling. Analisa bivariate using the chi square test.  Most of the mothers in Pampang village had negative attitudes as much as 51.1% and most of their husbands did not support as much as 64.3% and almost half of the respondents participated in family planning as much as 48.9%. A significant relationship between maternal attitudes  and husband support with family planning participation in Pampang Village is shown by p value: 0.002 < ?: 0.05, and p value 0.02 < ?: 0.05.